Resilience and mental health in female athletes: identification of associations needed for future longitudinal research - Stewart, T. M.; Wesley, N. Y.; Hazzard, V. M.; Varzeas, K. A.; Rowan, M.; Becker, C. B. (Exercise, Sport, and Movement, 2025)
Introduction Psychological resilience has been identified as a potentially modifiable trait/process that may enhance sport performance and athlete mental health. One barrier to improving resilience in female athletes is a lack of longitudinal research identifying upstream modifiable risk factors that can serve as intervention targets. Importantly, the field also lacks sufficient cross-sectional data to inform hypotheses about upstream risk factors. The primary purpose of this study was to address the gaps in both cross-sectional and longitudinal research aimed at enhancing resilience, with a focus on initial cross-sectional findings. This study also investigated whether resilience as assessed was associated with select mental health outcomes.